Contract farming and smallholder incentives to produce high quality: Experimental evidence from the Vietnamese dairy sector - Saenger, Christoph; Qaim, Matin; Torero, Máximo; Viceisza, Angelino (Wiley, 2013)
In emerging markets for high‐value food products in developing countries, processing companies search for efficient ways to source raw material of high quality. One widely embraced approach is contract farming. But relatively little is known about the appropriate design of financial incentives in a small farm context. We use the example of the Vietnamese dairy sector to analyze the effectiveness of existing contracts between a processor and smallholder farmers in terms of incentivizing the production of high quality milk. A framed field experiment is conducted to evaluate the impact of two incentive instruments, a price penalty for low quality and a bonus for consistent high quality milk, on farmers’ investment in quality‐improving inputs. Statistical analysis suggests that the penalty drives farmers into higher input use, resulting in better output quality. The bonus payment generates even higher quality milk. We also find that input choice levels depend on farmers’ socio‐economic characteristics such as wealth, while individual risk preferences seem to be less important. Implications for the design of contracts with smallholders are discussed.